2022
DOI: 10.3390/ijms232416070
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Artificial Intelligence to Investigate Targeted Nanoparticles’ Uptake in TNBC Cells

Abstract: Triple negative breast cancer (TNBC) is the most aggressive subtype of breast cancer in women. It has the poorest prognosis along with limited therapeutic options. Smart nano-based carriers are emerging as promising approaches in treating TNBC due to their favourable characteristics such as specifically delivering different cargos to cancer cells. However, nanoparticles’ tumour cell uptake, and subsequent drug release, are essential factors considered during the drug development process. Contemporary qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…With this in mind, DL algorithms are being used in precision medicine to predict anticancer drug response in patient-derived cancer cell lines, as in the case of the DeepDRK framework, which is freely available ( Wang Y et al, 2021 ). A method based on DL was developed to study the uptake of targeted nanoparticles in triple-negative breast cancer, which could be useful for proper dosing in clinical practice ( Ali et al, 2022 ). A nanodiamond biosensor platform using DL was developed to rapidly assess individual specific sensitivity to oxidative phosphorylation inhibitors in patients with hepatocellular carcinoma ( Xu et al, 2023 ).…”
Section: Machine Learning In Cancer Researchmentioning
confidence: 99%
“…With this in mind, DL algorithms are being used in precision medicine to predict anticancer drug response in patient-derived cancer cell lines, as in the case of the DeepDRK framework, which is freely available ( Wang Y et al, 2021 ). A method based on DL was developed to study the uptake of targeted nanoparticles in triple-negative breast cancer, which could be useful for proper dosing in clinical practice ( Ali et al, 2022 ). A nanodiamond biosensor platform using DL was developed to rapidly assess individual specific sensitivity to oxidative phosphorylation inhibitors in patients with hepatocellular carcinoma ( Xu et al, 2023 ).…”
Section: Machine Learning In Cancer Researchmentioning
confidence: 99%
“…Accuracy is the overall correctness of the model prediction and is calculated according to Equation (2) [32].…”
Section: Accuracymentioning
confidence: 99%
“…Nonetheless, prolonged CDDP exposure leads tumor cells to activate a variety of mechanisms to obstruct cisplatin, which is manifested at the molecular, organelle, and cellular levels ( Lugones et al, 2022 ; Romani, 2022 ; Tang et al, 2023 ). These mechanisms involve reducing platinum compound accumulation through active efflux/isolation or suppression of endocytosis; increasing oncogene mutagenesis; detoxifying through metallothionein, GSH conjugates, and other antioxidants; modulating DNA methylation status; increasing DNA-damage repair levels; altering protein post-translational modifications; over-expressing chaperone molecules; reinforcing compensatory signaling communication between organelles; suppressing apoptotic pathways; and activating the EMT pathway, among others ( Ali et al, 2022 ; Domingo et al, 2022 ; Tsvetkova and Ivanova, 2022 ). Numerous studies have now demonstrated that certain circular RNAs (circRNAs) are also involved in drug resistance of gynecologic cancer cells to CDDP ( Table 1 ).…”
Section: Circular Rnas and Gynecologic Cancer Chemoresistancementioning
confidence: 99%